2019
DOI: 10.3390/ijms20030551
|View full text |Cite
|
Sign up to set email alerts
|

Mettl3 Regulates Osteogenic Differentiation and Alternative Splicing of Vegfa in Bone Marrow Mesenchymal Stem Cells

Abstract: Bone mesenchymal stem cells (BMSCs) can be a useful cell resource for developing biological treatment strategies for bone repair and regeneration, and their therapeutic applications hinge on an understanding of their physiological characteristics. N6-methyl-adenosine (m6A) is the most prevalent internal chemical modification of mRNAs and has recently been reported to play important roles in cell lineage differentiation and development. However, little is known about the role of m6A modification in the cell dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
106
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(110 citation statements)
references
References 103 publications
4
106
0
Order By: Relevance
“…It was demonstrated that the deletion of METTL3 significantly promoted the pBMSCs adipogenesis process and janus kinase 1 (JAK1) protein expression via an m 6 A-dependent way (55) (Figure 2). Similarly, in Tian's study, it was shown that METTL3 was highly expressed in osteogenically differentiated BMSCs (54). METTL3 knockdown limited the expression of vascular endothelial growth factor (VEGF) and its bone formation-related splice variants (Vegfa-164 and Vegfa188) in osteoblast-induced BMSCs, which was implicated in the maturation of osteoblasts, ossification and bone turnover.…”
Section: A Modification Regulates Bone Developmentmentioning
confidence: 85%
See 1 more Smart Citation
“…It was demonstrated that the deletion of METTL3 significantly promoted the pBMSCs adipogenesis process and janus kinase 1 (JAK1) protein expression via an m 6 A-dependent way (55) (Figure 2). Similarly, in Tian's study, it was shown that METTL3 was highly expressed in osteogenically differentiated BMSCs (54). METTL3 knockdown limited the expression of vascular endothelial growth factor (VEGF) and its bone formation-related splice variants (Vegfa-164 and Vegfa188) in osteoblast-induced BMSCs, which was implicated in the maturation of osteoblasts, ossification and bone turnover.…”
Section: A Modification Regulates Bone Developmentmentioning
confidence: 85%
“…It is the most prevalent and internal modification that is tightly related to fundamental biological processes (Figure 1). M 6 A has recently been reported to play a part in pluripotency differentiation and development of the cell lineage (29,30,32,33), including osteogenic differentiation of bone marrow stem cells (BMSCs) (51,53,54). The human skeleton is a metabolically active tissue that undergoes continuous turnover and remodeling throughout life (48).…”
Section: A Modification Regulates Bone Developmentmentioning
confidence: 99%
“…A recent study indicated that silencing METTL3 markedly promoted the porcine BMSC adipogenesis process by targeting the JAK1/STAT5/C/EBPÎČ pathway via an m 6 A-YTHDF2-dependent regulatory pattern [23]. METTL3 depletion suppressed the osteogenic differentiation potential of BMSCs and decreased the expression of Vegfa splice variants [28]. In the present study, to investigate the effect of METTL3 on bone-forming function in an inflammatory environment, the osteogenesis process was evaluated in siMETTL3 treated osteoblasts with or without LPS.…”
Section: Discussionmentioning
confidence: 99%
“…A recent in vivo study demonstrated that the reduced m 6 A modifications in bone marrow mesenchymal stem cells (BMSCs) disrupt the osteogenic and adipogenic responses induced by parathyroid hormone, resulting in severe bone loss and excessive adipose accumulation [27]. Our previous study also showed that METTL3 loss inhibited the osteogenic differentiation potential of BMSCs [28]. Nevertheless, little is known about the role of METTL3 in osteoblast function during the inflammatory process.…”
Section: Introductionmentioning
confidence: 98%
“…As an RNA epigenetic modification, m 6 A has been indicated to be essential in regulating osteogenic differentiation. The results of our previous study demonstrated that attenuated m 6 A levels upon Mettl3 deficiency inhibits the osteogenic differentiation potential of bone mesenchymal stem cells (BMSCs) [31]. Another in vivo study using genetic murine models also shows that the conditional depletion of Mettl3 in BMSCs creates an osteopenia phenotype due to incompetent osteogenic potential [32].…”
Section: Introductionmentioning
confidence: 93%